2012
DOI: 10.1136/jnnp-2011-301386
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and psychopathology in myoclonus-dystonia

Abstract: The findings of this study suggest that anxiety disorders and executive dysfunctions may be part of the phenotype of M-D patients with a DYT11 mutation, whereas depressive symptoms and semantic fluency impairments may be secondary to suffering from a chronic movement disorder, regardless of DYT11 gene mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
65
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 60 publications
(47 reference statements)
5
65
2
2
Order By: Relevance
“…Underlying aetiology may be inherited, acquired or idiopathic (Albanese et al, 2013); with at least three causative genes identified and validated (including DYT1, DYT6, DYT25; Dauer et al, 2014) In addition to these often disabling motor symptoms, several studies have reported abnormalities in cognition (Stamelou et al, 2012). However, there has been some inconsistency in the abnormalities reported, with several conflicting findings, and some studies reporting no impairment at all (Ostrem et al, 2011;Taylor et al, 1991;van Tricht et al, 2012). Thus, the evidence for cognitive impairment in dystonia remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Underlying aetiology may be inherited, acquired or idiopathic (Albanese et al, 2013); with at least three causative genes identified and validated (including DYT1, DYT6, DYT25; Dauer et al, 2014) In addition to these often disabling motor symptoms, several studies have reported abnormalities in cognition (Stamelou et al, 2012). However, there has been some inconsistency in the abnormalities reported, with several conflicting findings, and some studies reporting no impairment at all (Ostrem et al, 2011;Taylor et al, 1991;van Tricht et al, 2012). Thus, the evidence for cognitive impairment in dystonia remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have also revealed scattered impairments, mostly on tests of executive functions. For example, Jahanashahi, Rowe and Fuller (2003) reported impairments in category fluency and dual tasking; Bugalho and colleagues (2008) reported an increased number of perseverations on the Wisconsin Card Sorting Test; and van Tricht et al (2012) reported impairment in category fluency and the Trail Making Test -part B. A few studies have also reported impairment in visual and verbal memory (Balas et al, 2006;Romano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mood disorders and psychoses have a higher prevalence in patients with rapid onset dystonia-parkinsonism (DYT12) than in non-mutant carriers 23,24 . Psychiatric non-motor features are also found in sporadic forms of primary dystonia.…”
mentioning
confidence: 99%